Dynamic Adjustment of CEO Incentives, Contracting Frictions, and Firm Performance - Bushman, Robert; Dai, Zhonglan; Zhang, Weining (The Accounting Review, 2025)
ABSTRACT We conceptualize equity incentive contracting as a dynamic process in which contracting frictions limit the speed at which equity incentives adjust to target levels. Slower adjustment speeds imply more prolonged deviations from value-maximizing targets and thus more severe negative effects on future performance. We find that contracting frictions significantly slow the speed of adjustment to target incentives (SOA). Consistent with frictions prolonging the persistence of deviations from target, we find that contracting frictions magnify the negative influence of deviations on future firm performance. Further, we find that the influence of contracting frictions on SOA operates through boards’ equity grant decisions. Our dynamic contracting perspective offers new insight into the relation between CEO incentives and firm performance by providing novel evidence that the speed of convergence to target incentives is a defining feature of the dynamic contracting process that translates inefficiency effects of contracting frictions into lower future performance. Data Availability: All data are publicly available from sources indicated in the text. JEL Classifications: M41.